Design of a Low-Cost Acquisition System to Reconstruct Images Through Electrical Resistance Tomography - Sepulveda-Palma, F; Acevedo-Cabello, J (IEEE Computer Society, 2020)
Electrical Resistance Tomography (ERT) is a technique employed in the industrial environment that reconstructs images formed by the impedance distributions inside a vessel. The method relies on measures from a data acquisition system, responsible to inject a current inside the vessel and measures the voltage on the boundaries, and sequentially an inverse problem solution. This paper introduces a low-cost design of an acquisition system that can obtain 30 images/s with a signal-to-noise ratio of 57.47 dB and a maximum error of 3.79%. It utilizes a simple RMS-to-DC converter demodulation scheme to provide good accessibility to researchers aimed at investigating flow patterns of multiphase flow applications. © 2003-2012 IEEE.